A Paradigm Shift in the Management of Thyroid Eye Disease How Teprotumumab Has Changed the Therapeutic Interface. Issue 1 (March 2022) - Ugradar, Shoaib; Kossler, Andrea L.; Douglas, Raymond; Cockerham, Kimberly
Abstract : Background: Teprotumumab, a monoclonal antibody that blocks the insulin-like growth factor-1 receptor, has recently been approved by the US Food and Drug Administration (FDA) for the treatment of thyroid eye disease (TED). Since its approval, aside from data on the safety and clinical efficacy of teprotumumab from Phase-2 and Phase-3 trials, only a handful of reports have been published regarding its use in the wider population. In this review, we briefly describe the mechanism of action of teprotumumab and review the literature to provide an overview of published clinical experience. This information was used to provide recommendations for patient selection, management of patient expectations, infusion details and site options, tips to optimize the authorization process, and how to monitor and mitigate side effects. Evidence Acquisition: A systemic review of the literature was performed regarding teprotumumab, focusing on its mechanisms of action and published reports on its use on patients with TED. A review of Embase, Medline (PubMed), Web of Science, and Google Scholar was conducted. Results: Clinical experience following the approval of teprotumumab has confirmed its efficacy in reducing inflammation and proptosis in patients with acute TED (<2 years). The reduction in proptosis occurs due to a reduction in orbital fat and muscle volume. Furthermore, there is evidence for its use in patients with compressive optic neuropathy. There are also reports that show its efficacy in reducing proptosis, inflammation, and diplopia in patients with chronic TED (>2 years). Teprotumumab was associated with side effects, such as muscle spasm, hearing loss, and hyperglycemia. To date, 2 case reports have shown a possible association with flares of inflammatory bowel disease. Conclusions: Teprotumumab is a powerful therapeutic option for the treatment of TED. Clinical experience following FDA approval has demonstrated efficacy in treating patients with acute and chronic TED. It is the only therapeutic option that has been shown to reduce orbital soft tissue expansion in TED. However, it is expensive, and sometimes, obtaining insurance authorization can be time consuming and difficult. Further work will reveal its full side effect profile and help to establish its role in the armamentarium used to treat TED. Abstract : Supplemental Digital Content is Available in the Text.